Spatio-temporal variability of tidal-stream energy in north-western Europe. (21st August 2020) - Guillou, Nicolas; Neill, Simon P.; Thiébot, Jérôme
Abstract : Initial selection of tidal stream energy sites is primarily based on identifying areas with the maximum current speeds. However, optimal design and deployment of turbines requires detailed investigations of the temporal variability of the available resource, focusing on areas with reduced variability, and hence the potential for more continuous energy supply. These aspects are investigated here for some of the most promising sites for tidal array development across the north-western European shelf seas: the Alderney Race, the Fromveur Strait, the Pentland Firth and the channels of Orkney. Particular attention was dedicated to asymmetry between the flood and ebb phases of the tidal cycle (due to the phase relationship between M2 and M4 constituents), and spring-neap variability of the available resource (due to M2 and S2 compound tides). A series of high-resolution models were exploited to (i) produce a detailed harmonic database of these three components, and (ii) characterize, using energy resource metrics, temporal variability of the available power density. There was a clear contrast between the Alderney Race, with reduced temporal variability over semi-diurnal and fortnightly time scales, and sites in western Brittany and North Scotland which, due to increased variability, appeared less attractive for optimal energy conversion. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.